Green Incentives for Climate Competitive Industries : A Practitioner’s Handbook - World Bank Group (World Bank, Washington, DC, 2016)
This handbook has been developed to provide instruction on the design and implementation of incentives for resource-efficiency purposes. The target audience is World Bank staff and stakeholders who are supporting the implementation of a resource-efficiency program in a country on behalf of the government, development finance institution (DFI) or other institution. It is intended to be applicable to most, if not all, resource-efficiency issues and incentives. However, it has a particular focus on energy-efficiency issues as this is the particular focus of the World Bank’s Climate Competitive Industries program, and is an area with a high level of interest from industry stakeholders. This handbook will help practitioners to understand: (i) why incentives should be used; (ii) the kinds of incentives that are available; (iii) how incentives can be combined; (iv) how to diagnose the resource-efficiency issues and potential for action in the country; (v) what the key considerations are in the selection and design on an incentive; and (vi) which institutional processes are required to support implementation of an incentive. It sets out the key considerations in designing and implementing an incentive for resource efficiency. Given the breadth of the potential areas of application, the handbook provides an introduction to each incentive type and sets out the skeleton approach to implementing an incentive. Further reading and support will be required at key stages to enable readers to undertake some of the technical aspects of implementation. For this reason, the handbook should be considered the entry point for any party considering an incentive scheme for resource efficiency. However, additional expertise may need to be sought when it comes to the actual design of a specific incentive.